Maximize prospect engagement with these best practices. Issue 11 (21st January 2016) - Burton, Emma
Abstract : With the number of college‐bound high school graduates reaching its lowest point in several decades, the competition for undergraduate and graduate students has become fierce. And while institutions compete for a shrinking applicant pool, they must now also capture the hearts and minds of a new generation of prospective students who are more digitally savvy and have higher "consumer" expectations than any generation before them. These Generation Zers are digital natives, accustomed to having information at their fingertips, near‐instantaneous response, and highly relevant and targeted consumer experiences for most of their lives.